2012
DOI: 10.1371/journal.pone.0053136
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Signaling Is Mediated by H2O2 and Cytosolic Ca2+ in the Salt Response of Populus euphratica Cells

Abstract: Extracellular ATP (eATP) has been implicated in mediating plant growth and antioxidant defense; however, it is largely unknown whether eATP might mediate salinity tolerance. We used confocal microscopy, a non-invasive vibrating ion-selective microelectrode, and quantitative real time PCR analysis to evaluate the physiological significance of eATP in the salt resistance of cell cultures derived from a salt-tolerant woody species, Populus euphratica. Application of NaCl (200 mM) shock induced a transient elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
93
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 58 publications
6
93
0
1
Order By: Relevance
“…Suppression of apyrase significantly altered the expression of genes involved in biotic stress responses (Lim et al, 2014). Additionally, our previous finding suggested that apyrase contributed to salt tolerance in P. euphratica (Sun et al, 2012b). NaCl shock elicited a significant rise in ATP in the ECM, but the eATP levels returned to basal levels after 20 min of salt treatment (Sun et al, 2012b).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Suppression of apyrase significantly altered the expression of genes involved in biotic stress responses (Lim et al, 2014). Additionally, our previous finding suggested that apyrase contributed to salt tolerance in P. euphratica (Sun et al, 2012b). NaCl shock elicited a significant rise in ATP in the ECM, but the eATP levels returned to basal levels after 20 min of salt treatment (Sun et al, 2012b).…”
mentioning
confidence: 78%
“…Additionally, our previous finding suggested that apyrase contributed to salt tolerance in P. euphratica (Sun et al, 2012b). NaCl shock elicited a significant rise in ATP in the ECM, but the eATP levels returned to basal levels after 20 min of salt treatment (Sun et al, 2012b). This was presumably due to ATP hydrolysis by ectoapyrase, which enabled P. euphratica to maintain low levels of eATP in a prolonged duration of salinity and, thus, prevent eATPinduced cell death (Sun et al, 2012a).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, some abiotic stress can also affect the release of ATP and the change of eATP level plays important roles in regulating the biotic stress responses. For example, Sun et al (2012b) found that salt shock induced a transient elevation in the eATP level, and eATP regulated a wide range of cellular processes required for salt adaptation. Thus, it seems likely that eATP is a central signal involved in the plant response to a variety of environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…A dozen studies showed that extracellular ATP signaling is associated with second messengers-cytosolic calcium (Ca 2+ ), reactive oxygen species (ROS), and nitric oxide (NO; Demidchik et al, 2003;Jeter et al, 2004;Song et al, 2006;Foresi et al, 2007;Wu and Wu, 2008;Reichler et al, 2009;Tanaka et al, 2010b;Tonón et al, 2010;Clark et al, 2011;Sun et al, 2012;Lim et al, 2014). Some of them are suggested to be mediated by cellular components in the plasma membrane, including Ca 2+ channels, heterotrimeric G Proteins, and NADPH oxidase (Song et al, 2006;Demidchik et al, 2009;Weerasinghe et al, 2009;Tanaka et al, 2010b;Hao et al, 2012;Wang et al, 2014).…”
mentioning
confidence: 99%